maths

posted by .

Prove that sin3theta=3sintheta-4sin^3theta

  • maths -

    prove sin (3Ø) = 3sin Ø - 4sin^3 Ø

    LS = sin(2Ø + Ø)
    = sin2Ø cosØ + cos2ØsinØ
    = 2sinØcosØcosØ + (1-2sin^2 Ø)sinØ
    = 2sinØ(1-sin^2 Ø) + sinØ - 2sin^3 Ø
    = 2sinØ - 2sin^2 Ø + sinØ - 2sin^3 Ø
    = 3sinØ - 4sin^2 Ø
    = RS

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. maths

    show that sin3theta-cos2theta =(1-sin theta)(4sin squared theta + 2sin theta -1)
  2. maths

    show that sin3theta-cos2theta =(1-sin theta)(4sin squared theta + 2sin theta -1)
  3. algebra

    Solve the equation for cos(3theta/2).tan(3theta/2)
  4. trig

    Solve the equation for cos(3theta/2).tan(3theta/2)for greater than or egual to zero but less than 2pi. Write your answer as a multiple of pi.
  5. math

    If 3 tan theta = 4, then evaluate : 3sintheta + 2costheta / 3sintheta – 2costheta
  6. math

    Prove that:(3-4sin^2A) (1-3tan^2A)=(3-tan^2A)(4cos^2A-3)
  7. sgmic

    Prove that tan theta+tan 2theta+tan 3theta=tan theta*tan 2theta*tan 3theta
  8. math

    cos^6A-sin^6A=cos2A(1-1÷4sin^2 2A) Prove
  9. Maths

    y = -14sin(8x)2cos(5x) - 4sin(5x)cos(8x) u = -14sin(8x) u' = -112cos(8x) v = 2cos(5x) v' = -10sin(5x) u2 = -4sin(5x) u'2 = -20cos(5x) v2 = cos(8x) v'2 = -8sin(8x) y' = (uv') + (vu') + (u2v'2) + (v2u'2) y' = [(-14sin(8x))(-10sin(5x)] …
  10. Maths

    Prove that cot(x/2)-3cot(3x/2)=4sin(x)÷(1+2cosx)

More Similar Questions